Use of ICT (Information and Communication Technology) in Improving the Quality of Learning in Early Childhood - Rubiatin; Hakimuddin Salim; Muhammad Wildan Shihab (al-Afkar, Journal For Islamic Studies, 2024)
Utilization of ICT in learning is the teacher's effort to provide interesting and enjoyable learning.  In early childhood, fun activities are needed to attract their interest in learning. Early age is a golden age during a child's development, this period is a phase where the child's growth develops very rapidly. Within this age range, education determines the child's next stage of development. The aim of this research is to determine the use of ICT as a learning medium for early childhood, where ICT is an interesting and enjoyable alternative learning medium that is of interest to children at Aisyiyah Bustanul Athfal II Kindergarten, Kupang City. This research uses qualitative research with case study design. This research focuses on the use of ICT as a learning medium at Aisyiyah Bustanul Athfal II Kindergarten, Kupang City. The findings from this research show that Aisyiyah Bustanul Athfal II Kindergarten students are very happy with the use of ICT as a learning medium, but the obstacle faced by schools is that there are some teachers who are not yet able to use ICT, but this obstacle can be minimized with the help of other teachers when learning.